Phase velocity of a pressure wave on the axis of an acoustic field of a circular ring in an acoustic baffle - WYRZYKOWSKI, Roman (Archives of Acoustics, 1986)
This paper is concerned with the so-called local velocity of a harmonicpressure wave of a. circular ring vibrating with a constant velocity amplitude.The ring is placed in an infinite rigid acoustic baffle. The local propagation velocity was calculated on the axis conducted from the center of the ring perpendicularily to its surface.The propagation velocity changes from infinity for z = 0 (singular point) to a constant value, c_0, for e equal to about 10 times the external radius of the ring.